A LITERATURE-BASED INVESTIGATION OF THE BRAIN-BASED LEARNING MODEL IN SCIENCE LEARNING - Solehah, Fadila Ismar; Irwandani, Irwandani; Pratama, Anisa Oktina Sari (Universitas Bhinneka PGRI, 2025)
This research seeks to evaluate the impact of the brain-based learning approach on science education. The method applied is a systematic literature review using the PRISMA model, utilizing various databases such as Google Scholar through the publish or perish application, Garuda, and scopus. A systematic literature review is used to conclude and provide recommendations that are relevant to issues related to the impact of brain-based learning models in science education from 2020-2024. The analysis demonstrated that the application of the BBL model had a positive effect on students' concept understanding and critical thinking skills, especially in Biology and Physics. Interest in BBL had decreased in 2022-2023 but increased again in 2023. This model is predominantly applied in senior high schools, although it is also effective in elementary schools to improve students' memory. Geographically, BBL is more optimal in Western and Central Indonesia, while Eastern regions face challenges related to facilities and teacher training. The BBL method can enhance the quality of science learning but requires more attention to teacher training and the provision of facilities.